2016
DOI: 10.1177/0010414016628269
|View full text |Cite
|
Sign up to set email alerts
|

Nationalism and Ethnic-Based Trust

Abstract: In diverse societies, individuals tend to trust coethnics more than non-coethnics. I argue that identification with a territorially defined nation, common to all ethnic groups, reduces the degree to which trust is ethnically bounded. I conduct a “lab-in-the-field” experiment at the intersection of national and ethnic boundaries in Malawi, which measures strength of national identification, experimentally manipulates national identity salience, and measures trust behaviorally. I find that shared nationality is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(16 citation statements)
references
References 110 publications
0
14
1
1
Order By: Relevance
“…Liberal nationalists often rely on the wellestablished association in social psychology between group identification and in-group trust (Foddy et al, 2009;Platow et al, 2012). However, only one experiment has shown that this applies to national identities specifically: in Malawi, Robinson (2016) found that making the overarching national identity salient heightened trust in co-nationals, including those from rivalling ethnic groups. Indeed, if we look at observational studies, the research front is divided between those who, using North American data, find that the link between national identity and trust is positive (Theiss-Morse, 2009;Johnston et al, 2010Johnston et al, , 2017, and those who, using cross-national data sets or case studies from Europe, on the contrary conclude that it is negative (Berg and Hjerm, 2010;Reeskens and Wright, 2013;Breidahl et al, 2018;Kongshøj, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liberal nationalists often rely on the wellestablished association in social psychology between group identification and in-group trust (Foddy et al, 2009;Platow et al, 2012). However, only one experiment has shown that this applies to national identities specifically: in Malawi, Robinson (2016) found that making the overarching national identity salient heightened trust in co-nationals, including those from rivalling ethnic groups. Indeed, if we look at observational studies, the research front is divided between those who, using North American data, find that the link between national identity and trust is positive (Theiss-Morse, 2009;Johnston et al, 2010Johnston et al, , 2017, and those who, using cross-national data sets or case studies from Europe, on the contrary conclude that it is negative (Berg and Hjerm, 2010;Reeskens and Wright, 2013;Breidahl et al, 2018;Kongshøj, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, they have not accounted for the strength of national attachment or pride. It is therefore difficult to synthesize their negative results with the largely positive ones from earlier studies, which by contrast measured national attachment or pride, but in turn neglected people's normative conceptions of their national identity (Theiss-Morse, 2009;Johnston et al, 2010Johnston et al, , 2017Robinson, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…94 Charnysh, Lucas, and Singh 2015;Mironova and Whitt 2014. At the same time, experimental research demonstrates how national or transnational identity can be more powerful than group interest defined by ethnicity or race (Prather 2020;Robinson 2016). Our finding that Japanese backlash against an apology to South Korea, despite shared race across the two countries, was stronger than US resistance toward an apology to Japan accords with this claim.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, language learning is packed using text of language attitudes with the goal of developing positive language attitudes that can arousing nationalism within a diversity frame. A strong and prominent national identity can overcome ethnic barriers to believe in diverse communities [31].…”
Section: Student Responsementioning
confidence: 99%